Power to the people: Local community initiatives and the transition to sustainable energy - van der Schoor, Tineke; Scholtens, Bert (Renewable & sustainable energy reviews, 2015)
The transition towards renewable and sustainable energy is being accompanied by a transformation of communities and neighbourhoods. This transition may have huge ramifications throughout society. Many cities, towns and villages are putting together ambitious visions about how to achieve 100% sustainable energy, energy neutrality, zero carbon emission or zero-impact of their communities. We investigate what is happening at the local community level towards realizing these ambitions from a social perspective. We use the case study approach to answer the following question: how do local community energy initiatives contribute to a decentralized sustainable energy system? We find that especially the development of a shared vision, the level of activities and the type of organisation are important factors of the strength of the ‘local network’.